2016
DOI: 10.1098/rstb.2016.0081
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phenotyping of infection-associated small non-coding RNAs

Abstract: Infection is a complicated balance, with both pathogen and host struggling to tilt the result in their favour. Bacterial infection biology has relied on forward genetics for many of its advances, defining phenotype in terms of replication in model systems. However, many known virulence factors fail to produce robust phenotypes, particularly in the systems most amenable to genetic manipulation, such as cell-culture models. This has particularly been limiting for the study of the bacterial regulatory small RNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…Tn-seq [81] or to monitor gene expression changes of host and pathogen during the course of infections using Dual RNA-seq [82]. While many non-coding RNAs are differentially regulated during infection, sRNA mutant strains often do not display strong macroscopic infection phenotypes [62,82,83]. Here, we demonstrated that deletion of the ptmG-regulating sRNA pair CJnc180/190 increases infection in the 3D tissue model in a way that is consistent with repression of PtmG levels by CJnc190.…”
Section: Discussionsupporting
confidence: 69%
“…Tn-seq [81] or to monitor gene expression changes of host and pathogen during the course of infections using Dual RNA-seq [82]. While many non-coding RNAs are differentially regulated during infection, sRNA mutant strains often do not display strong macroscopic infection phenotypes [62,82,83]. Here, we demonstrated that deletion of the ptmG-regulating sRNA pair CJnc180/190 increases infection in the 3D tissue model in a way that is consistent with repression of PtmG levels by CJnc190.…”
Section: Discussionsupporting
confidence: 69%
“…Finally, SgrS provides another example of how a core genome-encoded sRNA was recruited to regulate a horizontally acquired, S. enterica-specific virulence factor (189). SgrS base pairs with the mRNA of the secreted effector protein, SopD, via the same seed region used in E. coli and S. enterica for downregulation of the major glucose importer PtsG and other targets.…”
Section: Controlling Pathogenesismentioning
confidence: 99%
“…Intriguingly, while PinT does not produce a robust “macroscopic” replication phenotype in cell culture, the dual RNA-seq results show that PinT activity times Salmonella virulence gene expression shortly after invasion. We refer to this transcriptional signature as a “molecular phenotype” [ 27 ], which may represent a new approach to characterizing the role of gene products in infection. Of note, previous transposon mutagenesis studies in large animal models, including pigs, showed that pinT disruption is attenuating [ 28 ] despite the absence of an obvious phenotype in cell culture, illustrating the relevance of molecular phenotypes to studying disease in the absence of accessible model systems.…”
Section: Defining “Molecular” Phenotypes By Dual Rna-seqmentioning
confidence: 99%
“…For instance, with efficient multiplexing techniques [ 29 ], systematic virulence screens could be imagined that compare expression changes between infections with defined deletion strains of, say, every gene identified as a hit in transposon mutagenesis screens and the isogenic wild-type strain. Combining such ultra-high-throughput approaches will be a powerful strategy to define the molecular phenotypes of hundreds of pathogen genes in parallel, providing a rich basis for dissecting host–microbe interactions [ 27 ].…”
Section: Future Directionsmentioning
confidence: 99%